Energy disorders caused by mitochondrial dysfunction contribute to α-amatoxin-induced liver function damage and liver failure. (1st January 2021) - Chen, Xiao; Shao, Bing; Yu, Chengmin; Yao, Qunmei; Ma, Peibin; Li, Haijiao; Li, Bin; Sun, Chengye
Highlights: We explored whether α-amatoxin specifically damage the liver and hepatocytes. We established the mice metabolomics method based on GC–MS to understand the effect of α-amatoxin on the metabolism spectrum of hepatocytes. Two important time periods and four metabolic pathways were screened and identified by combining multiple data analysis and comparison. Molecular biology research verifying the accuracy of the most important pathways. The key role autophagy may play in liver injury induced by α-amatoxin has been discovered. Abstract: Mushroom toxicity is the main branch of foodborne poisoning, and liver damage caused by amatoxin poisoning accounts for more than 90 % of deaths due to mushroom poisoning. Alpha-amatoxin (α-AMA) has been considered the primary toxin from amatoxin-containing mushrooms, which is responsible for hepatotoxicity and death. However, the mechanism underlying liver failure due to α-AMA remains unclear. This study constructed animal and cell models. In the animal experiments, we investigated liver injury in BALB/c mice at different time points after α-AMA treatment, and explored the process of inflammatory infiltration using immunohistochemistry and western blotting. Then, a metabonomics method based on gas chromatography mass spectrometry (GCMS) was established to study the effect of α-AMA on liver metabonomics. The results showed a significant difference in liver metabolism between the exposed and control mice groups that coincided with pathological and biochemical indicators. Moreover, 20 metabolites and 4 metabolic pathways related to its mechanism of action were identified, which suggested that energy disorders related to mitochondrial dysfunction may be one of the causes of death. The significant changes of trehalose and the fluctuation of LC3-II and sqstm1 p62 protein levels indicated that autophagy was also involved in the damage process, suggesting that autophagy may participate in the clearance process of damaged mitochondria after poisoning. Then, we constructed an α-AMA-induced human normal liver cells (L-02 cells) injury model. The above hypothesis was further verified by detecting cell necrosis, mitochondrial reactive oxygen species (mtROS), mitochondrial permeability transition pore (mPTP) opening, mitochondrial membrane potential (Δψ m), and cellular ATP level. Collectively, our results serve as direct evidence of elevated in vivo hepatic mitochondrial metabolism in α-AMA-exposed mice and suggest that mitochondrial dysfunction plays an important role in the early stage of α-AMA induced liver failure.